2022
DOI: 10.3892/ol.2022.13641
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between immune‑related adverse events and treatment efficacy of anti‑PD1 immunotherapy in patients with esophageal squamous cell carcinoma

Abstract: Immune-related adverse events (irAEs) caused by immune checkpoint inhibitors (ICIs) are associated with improved treatment efficacy in certain types of cancer. In the present study, we assessed the association between irAEs and ICI efficacy. Patients with esophageal squamous cell carcinoma (ESCC) who received ICI treatment were stratified into irAEs and non-irAE groups. The objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A growing body of evidence from our group and others has demonstrated that the longitudinal development of irAEs during ICI therapies is often associated with improved outcomes with ICIs. 3-27 Ongoing efforts have centered around an integrated approach to identifying genomic, transcriptomic, and microbiome-associated predictors of irAEs. 28,29 More recently, deconvoluting the role of somatic and germline associations with irAEs is an area of emerging interest to understand the role of baseline genotypic and phenotypic features in augmenting ICI-associated irAEs among at-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence from our group and others has demonstrated that the longitudinal development of irAEs during ICI therapies is often associated with improved outcomes with ICIs. 3-27 Ongoing efforts have centered around an integrated approach to identifying genomic, transcriptomic, and microbiome-associated predictors of irAEs. 28,29 More recently, deconvoluting the role of somatic and germline associations with irAEs is an area of emerging interest to understand the role of baseline genotypic and phenotypic features in augmenting ICI-associated irAEs among at-risk individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, rash and pruritus always come out early, and most of these patients were proven pCR finally. Moreover, some literature did confirm that irAE is connected with better OS in melanoma ( 28 ), non-squamous NSCLC ( 29 ) and ESCC ( 30 ). The specific types of irAE might predict better prognosis as well, such as colitis and diarrhea ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICIs are immunotherapies that target immune cell surface checkpoints and enhance immunity through the use of antibodies to ‘tumor escape’, ultimately leading to an antitumor response by turning off the immune system’s braking mechanisms. 4347 An increasing number of studies have demonstrated the efficacy and safety of ICIs in patients with ESCC. In a phase III clinical trial of advanced ESCC second-line therapy (RATIONALE-302, NCT03430843), the use of tislelizumab was associated with improved OS and better safety compared to chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%